Development of real-time qPCR assays for detecting and quantifying common bacterial pathogens in fish from Mediterranean aquacultures - APOSTOLIDI, EVANGELIA D.; BITCHAVA, KONSTANTINA; TSAVEA, ELENI; BOUZALAS, ILIAS; GUBILI, CHRYSOULA; KREY, GRIGORIOS; BOUKOUVALA, EVRIDIKI (Mediterranean Marine Science, 2024)
The aquaculture industry is a rapidly developing and economically important sector for many countries, thus it requires effective solutions to overcome the key challenges that could impede its growth and sustainability. Among the most serious concerns are fish diseases caused by bacterial infections. This study introduces the development of novel rapid molecular methods employing Real-Time Polymerase Chain Reaction (qPCR) for the specific detection and quantification of five major fish pathogenic bacteria: Vibrio harveyi, V. alginolyticus, V. anguillarum, Photobacterium damselae, and Tenacibaculum maritimum. These bacteria are responsible for diseases such as vibriosis, photobacteriosis, and tenacibaculosis. The qPCR assays developed in this study are highly specific and extremely sensitive, making them suitable for early detection of these pathogens, thus aiding in the prevention of disease outbreaks in aquaculture farms.